Impact of Different Organic Extracts on Growth and Yield of Chili Pepper (Capsicum frutescens L.) - Muna Aied Yousif; Hussam Nafea Shakir (Iraqi Journal of Industrial Research)
There are many ways to increase the quality and productivity of the chili pepper plant, one of which is the use of organic fertilizer, to improve the properties of the soil as well as provide the nutrients needed. A pot experiment was carried out in the greenhouse of the Faculty of Agriculture, Samarra University, during the agricultural season 2022, with the aim of studying the effect of using seven types of fertilizers (bread yeast fertilizer A2, decomposed cow dung fertilizer A3, tea residue fertilizer A4, coffee residue fertilizer A5, rice soaked fertilizer A6, and chemical fertilizer A7in addition to the control A1) on the growth and yield of chili pepper using a randomized complete block design with four replications. The results were as follows: Fertilizer treatment A3 was significantly superior in vegetative growth characteristics, as the plant length reached 81.69 cm, stem diameter 7.95 mm, number of branches 10.75, and number of leaves 95.0 leaves. Plant- 1, leaf area 178.14 cm2, number of fruits 34.26 fruits. Plant- 1, and total yield 1.76 kg.plant-1, while treatment A2 excelled in the characteristics of root length 27.84 cm and root fresh weight 26.75 g. Fertilization treatment A4 had the lowest rate in all traits.